2009
DOI: 10.1021/bi802207t
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Kinetic Analysis of Substrate Specificity in Enterobactin Biosynthetic Lower Pathway Enzymes Provides Insight into the Biochemical Function of the Hot Dog-Fold Thioesterase EntH

Abstract: The Escherichia coli siderophore enterobactin is assembled from 2,3-dihydroxybenzoate (2,3-DHB) and L-serine by the nonribosomal peptide synthetases EntB and EntF. The processive thiol-template strategy used can be sabotaged by EntB misacylation. Through in vitro kinetic analysis we demonstrate two potential routes to EntB misacylation and provide evidence for two mechanisms by which the hotdog-fold thioesterase EntH can potentially prevent or reverse EntB misacylation.The siderophore enterobactin is synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 9 publications
2
45
0
Order By: Relevance
“…However, this seems unlikely because most hotdog TEs are specific for the hydrolysis of CoA thioesters (14,28). For instance, in vitro assays showed that the human hotdog fold TE (hTHEM2) is unable to hydrolyze ACP-loaded thioesters, although it has a broad tolerance for many CoA thioesters (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this seems unlikely because most hotdog TEs are specific for the hydrolysis of CoA thioesters (14,28). For instance, in vitro assays showed that the human hotdog fold TE (hTHEM2) is unable to hydrolyze ACP-loaded thioesters, although it has a broad tolerance for many CoA thioesters (14).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in vitro assays showed that the human hotdog fold TE (hTHEM2) is unable to hydrolyze ACP-loaded thioesters, although it has a broad tolerance for many CoA thioesters (14). Similarly, the EntH hotdog TE from the enterobactin biosynthetic pathway of E. coli shows no higher selectivity for substrate analogs loaded onto its cognate ACP than for substrates loaded onto CoA, indicating that the EntH TE recognizes the pantetheinyl portion of the substrates with few or no contact with the ACP (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, hotdog fold thioesterases are mainly known to utilize acyl-CoA as substrates, with only a few known examples that act on peptidyl carrier protein or ACP-tethered acyl substrates (23,41,42), including the EntH protein (or YbdB) involved in the biosynthesis of the non-ribosomal peptide-derived enterobactin (41,43,44). Hence, CalE7 appears to represent an uncommon example where a hotdog fold thioesterase was recruited for polyketide synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The bifunctional EntE catalyzes the adenylation of 2,3-DHB and the subsequent aroyl transfer to the pantetheine thiol of holo-EntB. Substrate ambiguity of EntD and EntE can derail enterobactin biosynthesis by leading to the formation of misacylated holo-EntB by two means: 1) when CoA is limited, endogenous acyl-CoA may substitute as a substrate for EntD (33), and 2) if 2,3-DHB is limited, a carboxylate metabolite may substitute as a substrate for EntE (34) (Fig. 1).…”
Section: Proofreadingmentioning
confidence: 99%